Petru Eşanu - emblematic personality of the Bessarabian music (Confluenţe Bibliologice, 2013)
The 70th anniversary of Petru Esanu birthday is a new opportunity to bring to the important moments (concerts, meetings, scientiﬁc papers) in the life and works of this emblematic personalities of the Bessarabian music.
Keywords: Eşanu Petru (1943); Bessarabian interpreters